Makna Subscriber Bagi Youtuber Kota Bandung - Achwan Noorlistyo Adi; Jenny Ratna Suminar; Nuryah Asri Sjafirah (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
Making an online video is one of the channelling ideas of creativity which is certainly owned by a video maker, including a YouTuber. A YouTuber will consider himself appreciated if someone else watches their video. Especially if the audience then becomes a loyal audience or subscriber of the YouTube Channel of the YouTuber. To get a large number of subscribers, of course, you need to work hard in creating creative contents, attract viewers, and have quality. These three things run with an uneasy process. Many out there think that becoming a YouTuber is enough to simply upload a video to YouTube without regarding to the aesthetics, concepts and creative processes of the video. Subscriber is also a benchmark for the success of YouTubers, as well as YouTubers in Bandung. YouTube itself gives several awards for YouTubers who can reach a certain number of subscribers. Seeing this phenomenon, the purpose of this research is to find out the meaning of subscribers for YouTubers in Bandung. This research uses a constructivist paradigm with qualitative approach, phenomenological methods and symbolic interaction theory. Data collection was taken by in-depth interviews with 4 Bandung YouTubers namely Kery Astina, Minyo, Eno Bening and Hisqie Furqoni. The meaning of the subscribers for the Bandung YouTubers is as a supporter, as a friend, as a determinant of the rate card indicator, and as a party that always gives feedback to YouTubers.